Fluid dynamics during Random Positioning Machine micro-gravity experiments. Issue 12 (15th June 2017) - Leguy, Carole A.D.; Delfos, René; Pourquie, Mathieu J.B.M.; Poelma, Christian; Westerweel, Jerry; van Loon, Jack J.W.A.
Abstract: A Random Positioning Machine (RPM) is a device used to study the role of gravity on biological systems. This is accomplished through continuous reorientation of the sample such that the net influence of gravity is randomized over time. The aim of this study is to predict fluid flow behavior during such RPM simulated microgravity studies, which may explain differences found between RPM and space flight experiments. An analytical solution is given for a cylinder as a model for an experimental container. Then, a dual-axis rotating frame is used to mimic the motion characteristics of an RPM with sinusoidal rotation frequencies of 0.2 Hz and 0.1 Hz while Particle Image Velocimetry is used to measure the velocity field inside a flask. To reproduce the same experiment numerically, a Direct Numerical Simulation model is used. The analytical model predicts that an increase in the Womersley number leads to higher shear stresses at the cylinder wall and decrease in fluid angular velocity inside the cylinder. The experimental results show that periodic single-axis rotation induces a fluid motion parallel to the wall and that a complex flow is observed for two-axis rotation with a maximum wall shear stress of 8.0 mPa (80 mdyne / cm 2 ). The experimental and numerical results show that oscillatory motion inside an RPM induces flow motion that can, depending on the experimental samples, reduce the quality of the simulated microgravity. Thus, it is crucial to determine the appropriate oscillatory frequency of the axes to design biological experiments.